A Light‐Activated Polymer Composite Enables On‐Demand Photocontrolled Motion: Transportation at the Liquid/Air Interface. (31st January 2019) - Ma, Shudeng; Li, Xiao; Huang, Shuai; Hu, Jing; Yu, Haifeng
Abstract: Swimmers at liquid/air interfaces have drawn enormous attention because of their potential applications. Described herein is one novel light‐driven swimmer based on a bimorph composite structure of a photoresponsive liquid‐crystalline polymer network and a commercially available polyimide (Kapton). The motion of the swimmer can be controlled by photoirradiation. The bilayer‐structured film shows quickly photoinduced bending towards the Kapton side upon exposure to UV light, and recovers immediately after removal of light. When placed on a liquid surface, the swimmer propels itself continually though rhythmic beating the liquid like a dolphin moving forward with its tail fin. Besides, light‐powered rotation of the swimmer is successfully achieved by simply changing the length‐width ratio and the irradiation site, mimicking the function of a dolphin's pectoral fin. Combining the forward movement and rotation motion together, on‐demand directional control of the photo‐driven swimmer can be readily obtained at room temperature, showing promise for miniaturized units for transportation. Abstract : Photogetriebene Schwimmer basierend auf einer bimorphen Verbundstruktur aus einem azobenzolhaltigen flüssigkristallinen Polymernetzwerk (LCN) und Kapton wurden entwickelt. Sie zeigen schnelle, kontinuierliche und dauerhafte Bewegungen an der Flüssigkeit/Luft‐Grenzfläche unter UV‐Bestrahlung und ermöglichen eine bedarfsgerechte Bewegungssteuerung bei Raumtemperatur, einschließlich Ein‐ und Ausschalten, Geschwindigkeit und Richtung.